Islam dan Kepemimpinan Nasional: Kontroversi Seputar Presiden Perempuan - Bahrul Ulum (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2019)
This article will highlight many problems on Islam and politics, especially around the arising debate on women president, the case: Megawati Soekarno Putri. The debates are very pierces as many component and element took parts including religious organization and the vest interests of political elements. The debates are of two sides: of traditional-revivalist in one side against its opponent, modernist-liberal, in other side. The first one is represented by the commoners and echoed by Islam puritans, like FPI, Laskar Jihad, Majelis Mujahiddin, and Kisdi. All of them are absolutely rejected women president. The later, represented by Modernist-Liberalist, obvisously supported by Moslems Liberal, in Indonesia.